Equality of women in rural household at different environmental geography - Hastuti Hastuti (Universitas Negeri Yogyakarta, 2016)
The research aimed to understanding the equality of women in rural households with environmental differences geography. Research location is in Brayut and Kaliadem, village with environmental differences geograhpy. Data were collected by structured interview structured interview data were analyzed descriptively quantitatively by using frequency tables, and descriptive qualitative data analysis in-depth interviews.The results showed, Brayut has a geography conducive environment characteristics, relatively flat, dominated wetland, better accessibility, land use competition tighter and more varied economic activities. Kaliadem geography has less conducive environment, dominated by dry land scattered with steep to very steep slope, accessibility is not good, the whole household livelihood from agriculture, livestock, and utilize the resources around. On the whole household outpouring of women's time for household activities more. Kaliadem outpouring husband's time to work on the most wealthy households and the outpouring of the time most women to work in poorer households. Household decision-making activities both hamlets compared dominant role of women over the role of men. Decision-making on agriculture and livestock in the men's role more prominent Brayut compared women, and in Kaliadem women and men have a balanced role. Investment activity is more prominent in Brayut. The involvement of women in public life does not necessarily affect the role of women in decision making and domestic public domain unless decisions on household activities.